Transforming Urban Mobility: Policy Strategies of Surabaya City Toward Environmentally Sustainable Urban Public Transport - Muhammad Eko Atmojo; Awang Darumurti; Saddam Rassanjani; Helen Dian Fridayani; Ahmad Kurniawan (Journal Public Policy, 2026)
The purpose of this study is to look at government policies in realizing environmentally friendly public transportation, especially public transportation that is integrated with waste management. The research method uses a qualitative method with a case study approach on public transportation in the city of Surabaya. Based on the results of the study, to realize a sustainable city and reduce congestion and waste in the city of Surabaya, the government has made a policy of paying for public transportation using plastic bottle waste. The use of payments with plastic bottles greatly helps the government in breaking down existing waste and encouraging people to use public transportation in the city of Surabaya, especially for the Suroboyo Bus. In addition, to support and strengthen environmentally friendly public transportation, the Surabaya City Government has begun to replace the fleet with electric public transportation. The change in transportation modes from fossil fuels to electricity is also government support in realizing sustainable public transportation in Indonesia. The conclusion of this study is that the government has a policy to reduce waste and congestion problems, one of which is by paying for public transportation using waste. To strengthen this policy, the government also integrates all urban transportation in Surabaya, with the GoBis application. The integration of public transportation management is the seriousness of the Surabaya City Government in overcoming urban problems.